Next Step towards a Learning Society? Impressions from the Boardwalk of Atlantic City - Abrahamsson, Kenneth ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
Impressions of Atlantic City can be used as an interesting case study for a discussion of the notion of a learning society and its survival in a policy-driven system like Sweden's and a market-influenced context such as Atlantic City. It would be interesting to draw a map of the different learning support systems that are available in various countries. It is a great challenge to analyze to what extent different societal contexts in the family, at work or at leisure, stimulate the curiosity and search for new knowledge. A majority of workplaces do not seem designed to enhance learning on the job and instead have a "low competence ceiling" and few expectations of individual initiatives. One's images of a learning society are greatly affected by the ideas, values, and economic motivation of different cultural and political systems. Atlantic City is an extreme outpost of a market-driven system with a very narrow-minded curriculum. The shortages of that learning context could be used to point out the need for learning rights for citizens. Among the learning rights could be free choice of subject and learning mission (particularly relevant in the face of employer-sponsored adult education), paid educational leave, and the option of full-time studies without staking one's total financial situation and security, day care, and social support. (CML)
ERIC Note: Paper presented at the Annual Conference of the American Association for Adult and Continuing Education (Atlantic City, NJ, October 1989).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Education; Civil Rights; Community Education; Comparative Education; Educational Policy; Educational Trends; Foreign Countries; Futures (of Society); Politics of Education; School Community Relationship; Sociocultural Patterns; Learning Society -- New Jersey (Atlantic City); Sweden; Opinion Papers; Speeches/Meeting Papers